Pengaruh Difusi Inovasi Klampid New Generation terhadap Kesadaran Tertib Administrasi Kependudukan di Kelurahan Karah - Gultom, Ferdi; Xaverius Sri Sadewo , Fransiscus; Imron , Ali; Handoyo , Pambudi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2026)
This study aims to explain the effect of Klampid New Generation innovation diffusion on population administration awareness. The research approach uses a quantitative approach to statistically test the effect of innovation diffusion attributes on population administration awareness. The analysis utilizes multiple linear regression to assess the effect of each independent variable on the dependent variable. Conducted in Karah Village, Jambangan Subdistrict, Surabaya City, the research involved 100 participants selected from the population of family heads using a non-probability sampling technique with a quota sample strategy. The results showed that the Klampid New Generation characteristics did not affect the population administration awareness. This explains that the technical superiority of service innovation does not necessarily increase population administration awareness. The adoption of innovations for change needs to involve stakeholders and the suitability of innovations to the needs of the social system